New species of Prototilla Schuster, 1949 from Argentina and diagnoses of the genus based on male and female (Hymenoptera: Bradynobaenidae: Typhoctinae: Eotillini) - Torréns, Javier; Fidalgo, Patricio; Roig-Alsina, Arturo; Brothers, Denis J. (Zootaxa, 2012)
Diagnoses for the genus Prototilla Schuster, 1949 based on males and females, new generic and specific characters, and descriptions of four new species (Prototilla nigra Torréns, Fidalgo, Roig-Alsina & Brothers, sp. nov. and P. intercalata Torréns, Fidalgo, Roig-Alsina & Brothers, sp. nov. based on males, and P. striata Torréns, Fidalgo, Roig-Alsina & Brothers, sp. nov. and P. telteca Torréns, Fidalgo, Roig-Alsina & Brothers, sp. nov. based on females) are provided. Prototilla typhoctoides (Martinez & Fritz, 1974), comb. nov. is transferred from Eotilla. A comparative table between the two genera of the tribe Eotillini and a key to the species of Prototilla are presented.